Using Remote Sensing Techniques and Geographic Information Systems in Changes Detection of Marsh Al Dalmaj Period 2000-2017 and Its Impact on Some Engineering Properties - Hassan, Zainab D.; Hassan, Shatha F. (Iraqi Journal of Science, 2024)
Al- Dalmaj area is a large water body in Iraq in the Afak district, which feeds from the general downstream between the Tigris and the Euphrates. The present study focused mainly on the changes detection in Al-Dalmaj area through analysis of the Landsat images for four selected years (2000, 2002, 2013 and 2017) to determine the changes in marsh waters, wetlands area, drylands areas and other land classes, The Landsat images of Al-Dalmaj area were analysed with the scene that includes the water surface and the area surrounded by the fixed geographical boundaries. The combination of remote sensing and GIS techniques have been found to be successful and effective in monitoring the spatial and temporal changes in land cover. These changes in the land cover of Al-Dalmaj area were detected using various analyses, including Normalised Difference Vegetation (NDVI), the Normalised Difference Water Index (NDWI), the Salinity Index(SI), and the Salinity ratio using Geographic Information Systems (GIS) programs v.10, using ERDAS Imagine v. 9.2 and spectral index techniques were used in this study to determine the land changes, to analyse Landsat images for the years (2000,2002,2013 and 2017). From the application of the equations of evidence referred to, it was found that the salinity (%) increased in the study area. 2002 represents the most extreme stage of the lack of natural conditions in Al- Dalmaj area. It was concluded that the water change was 83.8% for 2002 as 2000 as a reference. As for the natural vegetation, the percentage of change was 84.5% for the same year. The results showed that the percentage change in salinity was 127.5%, a high percentage compared to the rest of the study years. The bulk density values range between (0.70 - 0.89) Mg/m3.